Levels of Serum Ferritin & BMI as A Risk Factor For Developing of Gestational Diabeties Mellitus - Hajira Naila Rahu, Altai Khan Pathan, Anwar Ali Jame'', Bhojo Mai Tanwani, Salma Memon, Masood Nabi Noor , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To compare the ferritin levels between normal gravid women and women with diabetes mellitus (gestational) and to investigate the influence of elevated serum ferritin levels on the risk of diabetes mellitus (gestational ). Methods: This comparative cross-sectional study was carried out at Physiology Department of BMSI Jinnah Postgraduate Medical Center in cooperation with the department of Gynecology and Obstetrics ofJinnah hospital. Karachi. This study was performed on 60 gravid women of age ranging between 20-40 years and gestational age 28 weeks to 33 weeks, divided into two equal groups. Ferritin levels of subjects were measured through enzyme linked immunosorbent assy ( Elisa ), fasting and random blood glucose by enzymatic method & hemoglobin by Sahlis hemoglobinometer. Results: In women with diabetes mellitus (gestational ) levels of ferritin were significantly elevated as contrast to control group pregnant female. Serum ferritin was detected 70.3±77ng/m1 versus 19.8±0.31ngiml, fasting blood sugar 194.9 ± 0.81 VS 80.3 + 0.65 and random blood sugar 279.4±2.27 VS 109.7±1.11. Conclusion: Levels of ferritin were observed significantly greater in women with gestational diabetes mellitus in contrast to control group gravid women due to inflammation but not due to iron over load & inflammation created by higher BMI before pregnancy.